1988
DOI: 10.1016/s0166-9834(00)80043-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of methane over vycor glass, quartz glass and various silica, magnesia and alumina surfaces

Abstract: The reaction between methane and oxygen was investigated in empty Vycor glass and quartz tubes and over various silica compounds in powder form. In the temperature range of 893-993 K and with methane-to-oxygen ratios close to unity, formaldehyde, ethane and ethene were produced with a combined 53-96% selectivity over Vycor glass reactor surfaces. Quartz reactor surfaces were less active, but gave the same products. Silica compounds in powder form such as Cab-0-Sil, Ludox gels and silicic acid were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 21 publications
4
19
0
Order By: Relevance
“…An Arrhenius plot is given in Figure 4 for these catalysts. This activation energy value is very typical to the ones reported in the literature for different silica preparations (Kastanas, et al, 1988). The linear nature of this plot even at the highest conversion levels insures the absence of mass and heat transfer effects.…”
Section: Sio 2 Supportsupporting
confidence: 82%
“…An Arrhenius plot is given in Figure 4 for these catalysts. This activation energy value is very typical to the ones reported in the literature for different silica preparations (Kastanas, et al, 1988). The linear nature of this plot even at the highest conversion levels insures the absence of mass and heat transfer effects.…”
Section: Sio 2 Supportsupporting
confidence: 82%
“…An Arrhenius plot is given in Figure 5-35 for these catalysts. This activation energy value is very typical to the ones reported in the literature for different silica preparations (Kastanas, et al, 1988). The linear nature of this plot even at the highest conversion levels insures the absence of mass and heat transfer effects.…”
Section: Oxidation Of Methane By Fepo 4 Supported On Siosupporting
confidence: 82%
“…This trend seems to be based on a common sense that the silica materials are catalytically inert, but silica actually catalyzes a few reactions. [7][8][9][10][11][12][13] Recently, it was found that unmodified mesoporous silica has some advantages to amorphous silica, which has mild acidity [14][15][16] and radical-like function 17,18 to catalyze some reactions.…”
Section: Introductionmentioning
confidence: 99%